If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2 = 8(y + 7) Reorder the terms: 2 + 4y = 8(y + 7) Reorder the terms: 2 + 4y = 8(7 + y) 2 + 4y = (7 * 8 + y * 8) 2 + 4y = (56 + 8y) Solving 2 + 4y = 56 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 2 + 4y + -8y = 56 + 8y + -8y Combine like terms: 4y + -8y = -4y 2 + -4y = 56 + 8y + -8y Combine like terms: 8y + -8y = 0 2 + -4y = 56 + 0 2 + -4y = 56 Add '-2' to each side of the equation. 2 + -2 + -4y = 56 + -2 Combine like terms: 2 + -2 = 0 0 + -4y = 56 + -2 -4y = 56 + -2 Combine like terms: 56 + -2 = 54 -4y = 54 Divide each side by '-4'. y = -13.5 Simplifying y = -13.5
| 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 | | 3m^2-7m-40=0 | | -126+9x=39-2x | | -12-2x=-20 |